Chiasmus. Issue 1 (28th March 2012) - Connor, Steven
Taking its cue from Aristotle's twin statements only that which has soul in it can have voice, while yet not everything that is in the voice has soul in it, this article explores the expressive forms and forces of the veiled, fatigued, disfigured or denatured voice, in hissing, sobbing, grunting, croaking, howling or growling. My particular focus will be on the psycho-cultural fortunes of the voiceless velar fricative, the sound heard in the Hebrew 'ruagh' (breath, spirit) and the Greek 'chiasmus'.